A case report on traumatic diaphragmatic injury repaired with prolene mesh - Sharma, Dhruva; Sharma, Anil; Vaghela, Parth; Dixit, Sunil (International Surgery Journal, 2017)
Penetrating and blunt trauma rarely results into traumatic diaphragmatic hernia which oftenly undergo unrecognized. A 25 year old male admitted with chief complaints of difficulty in breathing since road traffic accident. Chest X-ray of the patient showed collapsed lung along with contents of abdomen in left hemithorax. Patient was stablised and contrast enhanced CT scan of chest was done which showed abdominal contents in left hemithorax with diaphragmatic injury on left side with no spillage of contents in thoracic cavity. Left posterolateral thoracotomy was done through 6th intercostal space. The abdominal contents were reduced back into the abdominal cavity with care and a circumferential tear of diaphragm was found with complete avulsion of diaphragm from chest wall anteriorly and laterally. Repair was done with prolene mesh as primary repair was not possible due to avulsion of margins from anterior and lateral walls. One left chest-drain was put which was removed on 3rd post-operative day. The patient was put on antibiotics in postoperative period and was started orally from 4th post-operative day after appearance of bowel sounds. The patient showed good recovery in postoperative period and was discharged on 8th postoperative day. Prompt diagnosis and surgical management is mandatory to avoid complications.